A peculiar case of intussusception in a pregnant woman: A diagnostic challenge - Firdaus Hayati; Asyraf Mohd Zuki; Lim, Ming Chin; Pradeep Chand Chandran; Nornazirah Azizan; Mohamed Arif Hameed Sultan; Muhamad Hud Muhamad Zin; Khasnizal Abdul Karim (Elsevier, 2023)
Adult intussusception presents a diagnostic challenge given its non-specific symptoms. It is not as common as in infants and young children. Traditionally, diagnostic steps are invariably fit for normal adults, but not in pregnancy which faces certain limitations. A 40-year-old pregnant mother, gravida 9 para 8 at 34-week gestation, complained of intermittent epigastric pain for 2 days, requiring hospitalization. She soon developed minimal per rectal bleeding that was ruled out as hemorrhoid. Imaging was limited due to her pregnancy status. She later developed spontaneous delivery to a premature baby. Computed tomography (CT) revealed an ileocolic intussusception, which was confirmed via exploratory laparotomy. Histology was consistent with inflammatory fibroid polyp. Acute abdomen in pregnancy can be due to various causes, thus a high index of suspicion and early CT abdomen might help in early diagnosis and treatment. The benefit of doing CT on the mother and the risk of CT on the fetus is to be weighed as the timely diagnosis can prevent bowel ischemia and reduce maternal morbidity and mortality. Surgery remains the definite management in adult intussusception and an exact diagnosis can be made during the operation.